Desenvolvimento de aplicativo para suporte às prescrições e orientações de fitoterapia no Brasil - Guerra, Samidayane Moreira (2019)
The use of medicinal plants in curing diseases is related to human evolution itself, since it’s use can be identified in all times, and in almost all of humanity. This dissertation was organized in 3 distinct stages: in the first stage of the study a systematic review was performed on the knowledge and practice of health professionals about phytotherapy prescription. This systematic review was necessary to determine the knowledge and attitudes of health professionals regarding the prescription and orientation of herbal medicine. We found 14 relevant studies. The professionals were evaluated through specific questionnaires, and in 11 studies the level of knowledge was 50%, other 3 studies were classified with low knowledge. Evidence from the systematic review has demonstrated the need for educational programs to integrate and strengthen phytotherapy content in existing curricula. In the second stage, a database was developed on phytotherapics and herbal formulations based on updated scientific articles (last 5 years), and based on the Vademecum of Nutrition, the Phytotherapeutic Memento and the Brazilian Pharmacopoeia. The third step consisted of developing the application for mobile devices in phytotherapy for health professionals from a stepwise development planning; the application was built using a programming framework aimed at mobile devices, including Android, using JavaScript technology. In view of these results, the content of the application was elaborate with 65 different pathologies, 71 medicinal plants, 248 formulas and 27 phytotherapics registered composing 24 screens with the necessary variables for the prescription. The application was name "FitoSmart". In view of the above, the application presents the main variables for the prescription of phytotherapy by health professionals. Thus, the proposed instrument could be a useful tool to qualify the phytotherapic prescriptions, bringing more agility to the health and safety professional in the interactions.